Dinamika Permainan Lato-Lato Perspektif Antropologi - Batubara, Muhammad Zusanri (Asketik: Jurnal Agama dan Perubahan Sosial, 2023)
The viral lato-lato game has become a hot topic of conversation in Indonesia. A traditional game that became popular again in late 2022 in Indonesia. The lato-lato game was played around 1960 in America and Europe, while in Indonesia it began to be played around 1990. The lato-lato game is loved by many people ranging from adults, teenagers, to children. This game was tested by the President of the Republic of Indonesia Joko Widodo and the Governor of West Java Ridwan Kamil during a working visit to Subang Regency. The purpose of this research is to examine the lato-lato phenomenon in Indonesia, the pros and cons of lato-lato games, and gadgets vs lato-lato. The research method used is qualitative research. Data collection in this research uses secondary data sources obtained through literature studies by tracing various accesses on the internet such as news, journals, Instagram, and relevant websites. The data analysis used is descriptive data analysis technique by describing, analyzing, and interpreting the data obtained. The findings in this research are that the lato-lato game began to develop in December 2022. The virality of this game is inseparable from the influence of game producers and social media. The revocation of PPKM (Enforcement of Restrictions on Community Activities) due to Covid-19 by the Indonesian government became a turning point for the community to move and interact with other communities. Through lato-lato games, children are influenced to leave gadgets so that they interact and socialize with the surrounding environment.